Pengaruh Brand Awareness, Brand Image, dan Brand Trust Terhadap Keputusan Pembelian - Nurlita, Febi; Arsyad, Annisa Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Ventela is a local shoe brand that is increasingly popular in Indonesia, known for its modern design and superior product quality, as well as affordable prices. This brand has succeeded in attracting the attention of young consumers, especially students and schoolchildren, with comfortable and stylish shoe products. Ventela focuses on developing shoes for everyday use that prioritize a balance between functionality and aesthetics. In the midst of increasingly tight shoe market competition, Ventela strives to strengthen its position and continues to innovate to attract more consumers. This study aims to analyze the effect of brand awareness, brand image, and brand trust on purchasing decisions for Ventela brand shoes among students of the Faculty of Social and Political Sciences, Mulawarman University. Sampling in this study used the purposive sampling method with a sample size of 100 respondents. The testing methods used are instrument testing, classical assumption testing, multiple linear regression analysis testing, and hypothesis testing with the help of the SPSS version 26 application. This research method is quantitative research with data collection through online questionnaire distribution. The results of this study show that (1) brand awareness has a significant positive effect on purchasing decisions, (2) brand image does not have a significant effect on purchasing decisions, and (3) brand trust has a significant effect on purchasing decisions for Ventela shoes and (4) the three independent variables (brand awareness, brand image, and brand trust) simultaneously influence purchasing decisions for Ventela shoes.